2020
DOI: 10.3390/app10082925
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Photodynamic Therapy Using a Diode Laser 635 nm as an Adjunct to Conventional Chemo-Mechanical Endodontic Procedures against Enterococcus faecalis Biofilm: Ex-Vivo Study

Abstract: The study aimed to evaluate the antimicrobial effect of photodynamic therapy (PDT) with the use of Toluidine Blue (TB) on extracted teeth infected with biofilms of Enterococcus faecalis. Fifty-four extracted teeth with single-roots and single canals were mechanically shaped, autoclaved, and contaminated with E. faecalis. They were randomly divided into six groups: two groups were negative and positive control groups, two groups were subjected to mechanical instrumentation and PDT with different pre-irradiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…However, lasers operating in the VL range have been used in endodontics, such as KTP lasers emitting at 532 nm that have been studied for sterilizing root canals [60,61] and He-Ne lasers at 633 nm that were used for Laser Doppler Flowmetry [62]. Another promising aspect of laser-aided endodontics is photodynamic therapy that involves the use of a photosensitive dye (photosensitizer) and a low-intensity laser light to achieve antibacterial and tissue disinfection effects within the root canal system [63,64]. Photosensitizers aid the rise in the absorption coefficient of water in root canals, making lasers effective in the VL region [63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, lasers operating in the VL range have been used in endodontics, such as KTP lasers emitting at 532 nm that have been studied for sterilizing root canals [60,61] and He-Ne lasers at 633 nm that were used for Laser Doppler Flowmetry [62]. Another promising aspect of laser-aided endodontics is photodynamic therapy that involves the use of a photosensitive dye (photosensitizer) and a low-intensity laser light to achieve antibacterial and tissue disinfection effects within the root canal system [63,64]. Photosensitizers aid the rise in the absorption coefficient of water in root canals, making lasers effective in the VL region [63].…”
Section: Discussionmentioning
confidence: 99%
“…Photosensitizers aid the rise in the absorption coefficient of water in root canals, making lasers effective in the VL region [63]. Diode lasers operating at 635 nm have shown promising efficiency in photodynamic endodontic therapy, where the photosensitizer has been combined with conventional chemo-mechanical debridement [64].…”
Section: Discussionmentioning
confidence: 99%
“…reported that TB when paired with a 635 nm diode laser enhanced the disinfection of E. faecalis in conventional endodontic surgery. 109 Another research by Sarda et al. focused on the effectiveness of various germicidal methods, including the use of diode lasers, MB-mediated aPDT and the chemical agent (sodium hypochlorite), as well as combinations of these methods.…”
Section: Applications In Oral Infectionmentioning
confidence: 99%
“…Using HELBO Blue Photosensitizer, which diffuses into biofilms, the walls of bacterial cells are stained with light-sensitive molecules. [27][28][29] Next, the molecules are activated using laser light with a wavelength of 670-690 nm and an energy density of 75 mW/cm 2 . 24 The absorption of light quanta by photosensitase molecules in the presence of oxygen leads to a photochemical reaction, as a result of which molecular triplet oxygen is converted into singlet oxygen, which destroys microorganisms in the biofilm.…”
Section: Introductionmentioning
confidence: 99%